Organisational Alignment as a Strategic Enabler in Advancing Employee Championing Behaviour Via Transformational Leadership - Roy, Noel Simon; Manimekalai, M.; Oommen, Jishin George; Gopakumar, B. (International Review of Management and Marketing, 2026)
This research explores the role of organisational alignment as a catalyst that strengthens the relationship between transformational leadership and employee championing behaviour. In today’s dynamic business environment, employees who actively advocate organisational goals and drive change are essential for sustaining innovation and adaptability. While transformational leadership inspires such proactive behaviour, its impact often depends on how well an organisation’s systems, culture, and strategy are aligned. Grounded in Social Exchange Theory, Role Theory, and Person-Organisation Fit Theory, this research examines how alignment enhances the translation of leadership vision into employee advocacy. Using a quantitative survey design, data were collected from employees across various sectors in South India and analysed through structural modelling techniques. The study integrates structural and psychological perspectives to explain how organisational alignment and factors such as trust, empowerment, and motivation enable employees to champion change. The findings contribute to leadership and organisational behaviour literature by positioning alignment as a critical enabler that connects leadership intent with employee action, offering valuable insights for building cohesive and high-performing organisations.